Deep Vein Thrombosis after Arbaeen Walking: A Case Report - Mohaddeseh Azadvari; Fatemeh Guitynavard; Seyede Zahra Emami-Razavi (Case Reports in Clinical Practice, 2026)
Deep vein thrombosis (DVT) is a serious medical problem that usually occurs in people who are immobilized, and its formation is not expected in people who do physical activity such as walking. Arbaeen walking is an event that takes place every year in Iraq over long distances and usually in hot and dry weather. During walking, there is a high probability of dehydration, which can be a risk factor for blood clots in the deep vessels. Since oral contraceptives also increase the possibility of blood clots in the vessels, it seems that women who use oral contraceptives and go for this walk, due to the possibility of concurrent dehydration, are at high risk for DVT. Due to the importance of this issue, we are currently introducing a case of a 44-year-old woman who suffered a DVT while taking a contraceptive while walking on Arbaeen.